2003
DOI: 10.4319/lo.2003.48.2.0594
|View full text |Cite
|
Sign up to set email alerts
|

Development of a deep chlorophyll maximum of Heterocapsa triquetra Ehrenb. at the entrance to the Gulf of Finland

Abstract: The development of a deep chlorophyll maximum (DCM) at a depth of 30-35 m was followed during a 15-d case study in July 1998 at the entrance to the Gulf of Finland. The study consisted of three 18-24-h periods of biological (chlorophyll a, phytoplankton, primary production), chemical (nitrate, phosphate) and physical (CTD, turbulence, vertical particle size distribution) measurements at an anchor station and six mesoscale towed CTD/ fluorometer mappings over the surrounding area. Exceptionally cold and windy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…These boundaries represent a rich source of inorganic nutrients and have stability properties favorable to H. triquetra accumulation. Kononen et al (2000) for example observed intense blooms of H. triquetra localized in 0.2 to 5 m thick layers 20 to 40 m below the surface of the water at the entrance to the Gulf of Finland in July 1998. Horizontal patch sizes were generally in the order of 1 km.…”
Section: Discussionmentioning
confidence: 99%
“…These boundaries represent a rich source of inorganic nutrients and have stability properties favorable to H. triquetra accumulation. Kononen et al (2000) for example observed intense blooms of H. triquetra localized in 0.2 to 5 m thick layers 20 to 40 m below the surface of the water at the entrance to the Gulf of Finland in July 1998. Horizontal patch sizes were generally in the order of 1 km.…”
Section: Discussionmentioning
confidence: 99%
“…Motile warm-water species of small cryptophytes and larger dinoflagellates, specifically the deep-water-inhabiting Heterocapsa triquetra and Dinophysis spp. (Carpenter et al 1995, Kononen et al 2003 were subdominant at that time. The periods of lower salinity during the VABP and LSBP were mainly caused by fresh-water runoff from the semi-enclosed inland basin nearby.…”
Section: Growth Seasonmentioning
confidence: 99%
“…This distribution pattern implies that dinoflagellate cells may perform asynchronous VM (AVM) with a period longer than 1 d. Moreover, the existence of persistent subsurface maxima of dinoflagellates near the pycnocline/nutricline has also been widely reported (e.g. Cullen & Horrigan 1981, Eppley et al 1984, Holligan et al 1984, Townsend et al 2001, Kononen et al 2003, indicating that some species of dinoflagellate simply stop migrating under certain environmental conditions (although active swimming is still required to maintain a particular depth without being dispersed by mixing). For the present discussion, subsurface aggregation is regarded as a special vertical migration pattern.…”
Section: Introductionmentioning
confidence: 99%